Strategi Pengembangan Daya Tarik Wisata Alam Puri Mataram sebagai Daerah Tujuan Wisata di Kabupaten Sleman Yogayakarta - Nina Mistriani (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia, 2020)
Potential Attraction of Puri Mataram Sleman Yogyakarta Regency is a trending topic for tourists as a tourist destination in Sleman Regency with the cultural concept of Mataram kingdom. Located in Drono. Tridadi village, Sleman, Yogyakarta. The research is to find out the strategy for developing natural tourist attraction. This research is qualitative research, applying facts in the field. Attraction of Puri Mataram get attention of the Indonesian Vice President in managing through BUMDes Tridadi Makmur increasing the construction activities, additions and management of infrastructure facilities that are balanced with increasing quality of services provided, making Puri Mataram a natural tourist attraction as a leading tourist destination in Sleman Regenc. Methods of approaching tourism components 5A (Accessibility, Accommodations, Attraction, Activities Amenities). The conclusion of a quality and balanced development strategy pays attention to 3 main steps, namely short-term focused emphasis, medium term emphasizing consolidation and long-term focus on development.